Peran Internet Financial Reporting dalam Meningkatkan Aktivitas Perdagangan Saham - Dewi Rejeki (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2026)
This study aims to examine the effect of Internet Financial Reporting (IFR) and the number of outstanding shares on stock trading frequency in technology sector companies listed on the Indonesia Stock Exchange during 2020–2024. This research uses a quantitative approach with purposive sampling, resulting in 6 companies and 30 observations. Data analysis techniques include descriptive statistics, classical assumption tests, and multiple linear regression using SPSS. The results indicate that IFR has a significant effect on stock trading frequency, while the number of outstanding shares has no partial effect. However, simultaneously both variables affect stock trading frequency. This study implies that transparency through IFR plays a crucial role in increasing trading activities